Separation of powers and constitutional judges: an approach of corrective roles - Figueroa Gutarra, Edwin (2015)
An approach of corrective roles of judges within the constitutional interpretation demands a number of parameters that must necessarily be made compatible with the principles, values  and guidelines pursuant to contemporary legal systems. This study covers the dimensions of these corrective roles in the attempt to set reference lines on the delicate task of the constitutional judges in the defense of the effective exercise of the fundamental rights and the regulations’ primacy of the Constitution. Finally, this study investigates if there is a jurisdictional government and to what extent the neoconstitutionalism turns out to be a relevant matter in the interpretation of the Constitution.